The role of stakeholder theory in project management while increasing the efficiency of government projects (Journal of Economic Research & Business Administration, 2019)
The relevance of project management is due to new challenges to the public administration system of the Republic of Kazakhstan. In modern conditions, the ability to realize the planned projects and tasks to achieve the set goals on time and within the established budgets becomes critical. Using the methods of project management, it is possible to mobilize and structure resources to increase efficiency in the implementation of government projects.The article discusses aspects of the use of project management in the activities of state bodies. Identification of shortcomings and solutions by using one of the project management tools as stakeholder management. The topic of stakeholder management is being actively developed by commercial institutions, which is due to a growing understanding of the role of stakeholders in the business of the company as a whole. However, with regard to the use of the theory of stakeholders in the implementation of state projects, the topic is not well developed.Consideration of the theory of stakeholders to solve the problems facing public authorities, due to new challenges in the public administration of the country. Effective interaction of the state with all interested parties in the implementation of state projects helps to reduce various risks and ensure social and economic stability in society.